1980
DOI: 10.1111/j.1476-5381.1980.tb08721.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rmi 12330a, a New Inhibitor of Adenylate Cyclase on Myocardial Function and Subcellular Activity

Abstract: RMI 12330A, a lactam‐imine, at concentrations of 10−4 m and higher, inhibited basal as well as isoprenaline and NaF‐stimulated adenylate cyclase activity of guinea‐pig heart homogenates. However, RMI 12330A was a more potent inhibitor of histamine‐stimulated adenylate cyclase (IC50 of 1.5 × 10−5 m). In the isolated work‐performing heart of the guinea‐pig, RMI 12330A (IC50 of 1.1 × 10−6 m) depressed all cardiac functions: pressures developed, dP/dt, contractile force, dF/dt, work performance and stroke work. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Our previous work indicated that the NO donor was functioning independently of cyclic GMP (23). In evaluating the possible involvement of cyclic AMP we utilized a number of different adenylyl cyclase modifiers including the cycloalkyl lactamamide, MDL-12330A, which has been utilized widely as an irreversible adenylyl cyclase inhibitor (35)(36)(37). Surprisingly, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work indicated that the NO donor was functioning independently of cyclic GMP (23). In evaluating the possible involvement of cyclic AMP we utilized a number of different adenylyl cyclase modifiers including the cycloalkyl lactamamide, MDL-12330A, which has been utilized widely as an irreversible adenylyl cyclase inhibitor (35)(36)(37). Surprisingly, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…cis ‐ N ‐ (2 ‐ phenylcyclopentil) ‐ azacyclotridec ‐ 1en ‐2‐amine monohydrochloride (MDL 12,330A) has been shown to block adenylyl cyclase in numerous preparations (e.g. Grupp et al ., 1980 ; Satake et al ., 1996 ). Addition of MDL 12,330A (50 μ M ) caused an increase in tone (to 235±34% of the basal level) ( n =18), suggesting ongoing production of cyclic GMP in these muscles (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Among adenylyl cyclase inhibitors, the original report identifying MDL-12,330a described an adenylyl cyclase-independent effect on the Na 1 , K 1 -ATPase (Grupp et al, 1980), and a more recent study identified an off-target effect on glycine transport (Gadea et al, 1999). As these inhibitors are used more widely, nonspecific effects become appreciated; for example, a recent report found that SQ22,536 has an effect on ERK activation unrelated to cAMP signaling (Emery et al, 2013), and two recent reports described sAC-independent effects of KH7 (Tian et al, 2011;Di Benedetto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%